AN APPLICATION OF A CULTURALLY RESPONSIVE TEACHING (CRT) APPROACH TO DRAMA TEACHING BASED ON LOCAL WISDOM: A STUDY AMIDST THE NEW NORMAL CONDITION OF THE COVID-19 PANDEMIC - Ndandara, Alfriani; Hambandima, Erny S.N. (Lire Journal (Journal of Linguistics and Literature), 2021)
The diversity of ethnicities and cultures characterizes the Indonesian nation as a multicultural nation. The peculiarities of each of these varieties can be found in the forms of social practice of social life. The values ??that are upheld in every social practice of social life also underlie the development direction of national development sectors. It is stated in the National Education System Law of 2003 to organize National Education which is rooted in the religious values ??and national culture of Indonesia, especially in the field of education. The mandate realization of this law is stated that the content of the curriculum contains local potentials. These two mandates underlie curriculum principles and color educational practices to reflect the diversity existed in Indonesia. This research is entitled An Application of Cultural Responsive Teaching (Crt) Approach To Drama Teaching: A Study Amidst the New Normal Conditions of the Covid-19 Pandemic. The approach was introduced by Geneva Gay (2011: 188-214) as an approach that emphasizes the importance of learning based on students’ cultural backgrounds. Multicultural education is a concept that underlies this approach (Baker, 1996: 374). The research framework is the application of CRT approach to learning activities in Drama Course. This research used a qualitative descriptive approach. The results of this study resulted in several things discussed from the aspects of preparation, personal character, presentation, interaction between teachers and students and local story script products. It is hoped that this research will produce a learning framework that integrates elements of local culture for teaching drama.